PERSEPSI REMAJA TERHADAP TAYANGAN PORNOGRAFI DI TELEVISI (STUDI DI TIGA SEKOLAH MENENGAH ATAS DI KOTA PALU, PROVINSI SULAWESI TENGAH) - Achmad Herman (Jurnal Ilmu Komunikasi, 2008)
The pornography context previously and up to now still becomes a huge controversion in our society which is complicated to be in the same point of view. Because there are many vari- ables which influence the concept, moreover in determining the way of policy, such as culture and custom. Basically, there should be a tool that control (social control) the behavior in order that it can be responsible, particularly for those kinds of thing in expressing the moral value of sexuality and sensuality. Because there are commonly perspective which are always used to analyze or to discuss teh concept of pornography, they are mart point of view and pornography it self (religion, culture, custom, etc). This research intends to know the teenagers perception related to the pornography depic- tions on the television programmes and also want to know their responses according to the television programmes which contain of pornography. This research is designed particularly for teenager between 16-18 years old and it was researched in three of senior high school in Palu, Central Sulawesi. The sample were collected is stratified random sampling by giving the criteria to make the social class of the whole population. The result shows that the teenagers thought that most of the television programmes such as film (41,8% male and 33,3% female) and “sinetron” (15,4% male and 20,6% female) contain of pornography. Because ther are many erotic scenes like kissing and showing the breast which is not approriate to be showed in public area.